A new species of Lycoderes Sakakibara (Hemiptera, Membracidae, Stegaspidinae) from Brazil - Creão-Duarte, Antonio José; Cabral, Valberta Alves; Lourenço, Aline (Zootaxa, 2017)
A new species of treehopper is described and illustrated: Lycoderes albinoi sp. nov. (from Una, Bahia, Brazil). A previously published key to Lycoderes species is modified to include this new species. The female of Lycoderides capixaba Sakakibara, 2013 is also described for the first time.